Engineering of service processes through designing simulation experiments. Issue 1 (1st January 2011) - Kaner, Maya; Gadrich, Tamar; Dror, Shuki
Service processes encompass a large number of variegated factors. These elements and their interactions have to be considered when engineering a service process. We propose a methodology that allows designers to design simulation experiments through which they can handle various service factors and their interactions in action and thereafter propose process improvements based on a generic analysis scheme. Our methodology deals both with conceptual and detailed designs of service processes and enables the designer to define process factors schematically and simulate possible scenarios based on variations in these factors. We present the application of our methodology to the engineering of a customer order handling process.